2019
DOI: 10.1093/dote/doz083
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal melanoma: a systematic review and exploratory recurrence and survival analysis

Abstract: SUMMARY Esophageal melanoma is a rare and poorly described malignancy. We sought to review all available data on the clinicopathological features, management options, and outcomes of patients with esophageal melanoma to guide clinicians working to treat these uncommon tumors. A systematic literature search of the PubMed, Embase, and Cochrane databases was performed. Exploratory recurrence and survival analyses were performed using previously-validated pooled Cox and logistic regression technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
0
20
0
2
Order By: Relevance
“…Most primary gastrointestinal melanomas have been identified in the oral mucosa and anorectal region. PEM is exceedingly rare; less than 200 cases have been reported in the literature 5 , 6 . It is not only considered a rare subtype of primary melanoma but also accounts for an unusual primary gastrointestinal malignancy as PEM represents 0.1% of all primary esophageal tumors 4 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most primary gastrointestinal melanomas have been identified in the oral mucosa and anorectal region. PEM is exceedingly rare; less than 200 cases have been reported in the literature 5 , 6 . It is not only considered a rare subtype of primary melanoma but also accounts for an unusual primary gastrointestinal malignancy as PEM represents 0.1% of all primary esophageal tumors 4 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, no association between PEM and known carcinogens such as alcohol and tobacco have been recognized in the literature. It occurs more frequently in men than women with an average ratio of 2:1 around the 6 th decade of life and has a predilection for the Japanese population 5 . Although melanocytes are mainly skin and choroid bound, Ohashi et al demonstrated in their study that these highly specialized cells can be found in the lower esophagus of up to 8% of healthy Japanese patients 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations